Synthesis and photodiode properties of chalcone substituted metallo-phthalocyanine - Demirol, Murat; Sirka, Lutfiye; Caliskan, Eray; Biryan, Fatih; Koran, Kenan; Gorgulu, Ahmet Orhan; Yakuphanoğlu, Fahrettin (Elsevier, 2020)
In this study, we aimed to investigate the photodiode properties of the chalcone substitutedphthalocyanine complex due to the important physical properties of the phthalocyanine and chalcone compounds. For this purpose, in the first step, a heterocyclic chalcone compound (HC) bearing a pyridine and hydroxyl group was obtained from the reaction of 40-hydroxyacetophenone with pyridine-3 aldehyde. In the second step, the chalcone-substituted phthalonitrile compound (HCA) was obtained by interacted 4-nitroftalonitrile with the compound HC in the presence of K2CO3 in DMF in an argon atmosphere. The new chalcone substituted metallo-phthalocyanine (HCA-Co) was synthesized from the reaction of compound HCA with Co (II) acetate according to heating of solid phase method under an inert atmosphere. The structure of HC and HCA-Co were fully characterized by using H-1, and C-13-APT NMR, FTIR, elemental analysis, UV-Vis spectroscopy. The HCP-Co thin-film planar heterojunction diode was prepared. The organic layer was deposited onto the p-Si substrate to obtain an Al/p-si/phthalocyanine(HCP-Co)/Al diode. The current (I)voltage (V) characteristics of heterojunction diode was measured under dark and illuminated conditions (20-100 mW/cm(2)) at room temperature. The electrical characteristics of the device were measured. The ideal factor value was found to be 5.20 and according to this value, the diode exhibits non-ideal behavior. The frequency dependence of capacitance and the role of interface states were examined. The results showed that chalcone substituted metallo-phthalocyanine has a photodiode and photocapacitor characteristic. Therefore, chalcone-linked metallo-phthalocyanine can be applied in solar tracking systems. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: Phthalocyanine; Photodiode; Chalcone; Photo-physical; Synthesis